Oxidative Stress and Enantioselective Degradation of Dufulin on Tubifex. (16th September 2020) - Jiang, Xiaoxia; Song, Bangyan; Wang, Shouyi; Ran, Lulu; Lu, Ping; Hu, Deyu
Abstract: Dufulin is a new type of chiral antiplant virus agent independently developed in China. The present study was conducted to determine the effects of different concentrations of rac ‐dufulin and dufulin enantiomers (1, 5, and 10 mg/L) on oxidative stress in Tubifex after exposure for 3, 7, and 14 d. Results showed that rac ‐dufulin and individual enantiomers had no significant effects on total protein content and glutathione reductase activities. Increased superoxide dismutase demonstrated the generation of superoxide anion radical. The increase in glutathione S ‐transferase may be due to detoxification mechanisms. The different changes in catalase activities could be due to oxidative stress. The increase in malondialdehyde may be due to the accumulation and toxicity of contaminations. The degradation behavior of dufulin enantiomers was studied through spiked‐water and spiked‐soil tests. The degradation rate of S ‐(+)‐dufulin was faster than that of R ‐(−)‐dufulin. The present study demonstrated the occurrence of enantioselectivity in the degradation and oxidative stress of dufulin to Tubifex . In spiked soil, the concentrations of dufulin enantiomers in underlying soil were significantly higher than those in overlying water; but after 5 d of degradation, the bioturbation of Tubifex could facilitate part of dufulin diffusing from the underlying soil into the overlying water and altered the partitioning of dufulin. The present study provided a basis for conducting environmental safety risk assessments and rationally using dufulin as a chiral pesticide. Environ Toxicol Chem 2020;39:2136–2146. © 2020 SETAC